POLICY AND LINGUISTIC CONSIDERATIONS IN THE PROPOSED RENAMING OF WEST JAVA PROVINCE TO TATAR SUNDA - Sarip, Sarip; Fitriana, Diana; Azhari, Aidul Fitriciada; Absori, Absori; Dewi, Elya Kusuma; Adiantika, Hanif Nurcholish; Nurkhaeriyah, Nurkhaeriyah (Cepalo, 2024)
This legal study investigates the implications of the proposed renaming of West Java Province to Tatar Sunda Province, employing the approach of intuitive semantic dualism to address issues of language, territory, ethnicity, and national identity. The research draws on data from academic journals, books, media reports, and interviews, comparing secondary data with field opinions on the languages and bordering regions of the Sundanese dialect. The findings reveal that, although the Sundanese linguistic system was expected to play a crucial role in the renaming process and promote territorial unity, it falls short due to the inclusion of regions such as Banten, pre-independence Batavia, and bilingual border areas in the east and north. This geographic and linguistic complexity means that the name "Tatar Sunda" does not accurately reflect the distinct linguistic, cultural, and territorial identities of the Sundanese people as described by J. van Baal. Legally, while there are no barriers to the renaming policy, the proposed name fails to adequately represent the region's diverse identities. Consequently, the study recommends further exploration of more representative alternatives that align with the existing legal framework, ensuring that the name change is not only legally valid but also appropriately reflects the region's identity.